2021
DOI: 10.1152/jn.00320.2021
|View full text |Cite
|
Sign up to set email alerts
|

Inducing neuroplasticity through intracranial θ-burst stimulation in the human sensorimotor cortex

Abstract: The progress of therapeutic neuromodulation greatly depends on improving stimulation parameters to most efficiently induce neuroplasticity effects. Intermittent Theta Burst stimulation (iTBS), a form of electrical stimulation that mimics natural brain activity patterns, has proved to efficiently induce such effects in animal studies and rhythmic Transcranial Magnetic Stimulation studies in humans. However, little is known about the potential neuroplasticity effects of iTBS applied through intracranial electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Understanding how TBS-patterned direct electrical stimulation induces plasticity in humans, remains critical but limited in humans in vivo, particularly in the frontal lobe. Previous studies in epilepsy patients evaluated the effects of TBS in the sensorimotor cortex, revealing modifications in beta-frequency coherence 56 . While other iEEG studies have examined TBS-induced oscillatory changes, notably increasing theta band power 12,100 , the voltage effects of TBS and the dynamics of these neural responses within and across stimulation trains remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding how TBS-patterned direct electrical stimulation induces plasticity in humans, remains critical but limited in humans in vivo, particularly in the frontal lobe. Previous studies in epilepsy patients evaluated the effects of TBS in the sensorimotor cortex, revealing modifications in beta-frequency coherence 56 . While other iEEG studies have examined TBS-induced oscillatory changes, notably increasing theta band power 12,100 , the voltage effects of TBS and the dynamics of these neural responses within and across stimulation trains remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…This approach provides anatomically precise information about neuronal populations at a millimeter scale and temporally precise information on neural dynamics at a millisecond scale. Direct electrical TBS-patterned stimulation paired with iEEG measurements have found lasting entrainment of frequency-specific oscillations (in the theta band, 4-8 Hz) after TBS 12 , TBS-specific induced buildup of beta band coherence in the sensorimotor cortex 56 , and improvement in memory within a learning and memory task via TBS microstimulation of medial temporal lobe structures 8 . Crucially, the location of the TBS-specific responses were highly correlated with brain functional connectivity to stimulation 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 Intermission θ-burst stimulation (iTBS) is a novel stimulation mode of repetitive transcranial magnetic stimulation (TMS). 14 Koch et al 15 reported that cerebellar iTBS can regulate excitability in the posterior parietal cortex. Kim et al 16 used 1-Hz repetitive TMS (rTMS) to stimulate the cerebellum and found that conventional inhibitory rTMS can improve walking and balance function in patients with post-stroke ataxia.…”
mentioning
confidence: 99%